2021
DOI: 10.22270/jddt.v11i4-s.4964
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of UV-Spectrophotometric and RP-HPLC method for simultaneous estimation of Metformin and Doxycycline in bulk and synthetic mixture

Abstract: A simple, rapid, sensitive, accurate and precise UV spectrophotometric and isocratic RP-HPLC method have been developed for simultaneous estimation of Metformin and Doxycycline in bulk and synthetic mixture. Spectrophotometric estimation was done by two methods. First method was Q-absorbance ratio method, where two wavelengths 236 nm (λmax of Metformin) and 248 nm (Iso-absorptive point) were used. The second method was first derivative method. In this method the zero-crossing point of Metformin was selected at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…From the filtered solution, 1ml was pipetted out into a 10 ml volumetric flask and made upto 10ml with diluents 13 . Assay Method: Assay of the marketed formulation was carried out by injecting sample 14 corresponding to equivalent weight into HPLC system [15][16][17][18][19][20][21][22][23][24][25] Selection of Solvent: Metformin and Saxagliptin are marketed as combined dosage formulations. different solvents are used for the solubility of drugs, it was found that both the drugs are freely soluble in acetonitrile 15 .…”
Section: Methods Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…From the filtered solution, 1ml was pipetted out into a 10 ml volumetric flask and made upto 10ml with diluents 13 . Assay Method: Assay of the marketed formulation was carried out by injecting sample 14 corresponding to equivalent weight into HPLC system [15][16][17][18][19][20][21][22][23][24][25] Selection of Solvent: Metformin and Saxagliptin are marketed as combined dosage formulations. different solvents are used for the solubility of drugs, it was found that both the drugs are freely soluble in acetonitrile 15 .…”
Section: Methods Developmentmentioning
confidence: 99%
“…Assay Method: Assay of the marketed formulation was carried out by injecting sample 14 corresponding to equivalent weight into HPLC system [15][16][17][18][19][20][21][22][23][24][25] Selection of Solvent: Metformin and Saxagliptin are marketed as combined dosage formulations. different solvents are used for the solubility of drugs, it was found that both the drugs are freely soluble in acetonitrile 15 . Preparation of Buffer: Accurately weighed 1.36gm of Potassium dihydrogen orthophosphate was transferred into a 1000mlof Volumetric flask, about 900ml of milli-Q water was added and sonicate 9 to degassed and finally make up the volume with water.…”
Section: Methods Developmentmentioning
confidence: 99%
“…Various analytical methods have been reported in literature included estimation of Doxycycline in pure and dosage forms, including highperformance liquid chromatography (NP-HPLC and RP-HPLC) (Ghidini et al, 2018;Mileva, 2019;Mashru and Koshti, 2021;Dil et al, 2020), HPLC-mass (Permana et al, 2019), HPTLC (Kumssa et al, 2021), potentiometric sensor (Ali et al, 2018), ratiometric probe (Tian and Fan, 2021), flow injection spectrophotometry (Tawfeeq and Qassim, 2020), Fluorometric (Sun, 2018) and the spectrophotometry methods using various reagents: Fe(II) with 1,10-phenanthroline (method A) and Fe (II) with 2,2'-bipyridyl (method B) (Awad and Taki, 2021), 4-aminoantipyren in presence of potassium ferriecyanide in alkaline medium. (Al-Kalissy and Mohammed, 2015) diazotized benzocaine (Abbas et al, 2020) and UV-spectrometric method at 260 nm (Patil et al, 2020), simultaneous estimation of doxycycline and levofloxacin using wavelengths 273 nm and 287nm in measurements respectively, and iso-absorptive point at 280 nm in phosphate buffer pH 6.8 prepared in Water: Methanol (80:20) (Gholse et al, 2022), Some of the previous methods required heating, and some of them needs expensive apparatus, therefore we developed spectrophotometric method for the estimation of doxycycline as pure and in its dosage form, based on oxidative coupling reaction using 4-aminoantipyrene as a reagent and in the presence of potassium periodate.…”
Section: Scheme (1)mentioning
confidence: 99%